Chemical Genetics Screen Identifies COPB2 Tool Compounds That Alters ER Stress Response and Induces RTK Dysregulation in Lung Cancer Cells. Issue 23 (19th November 2021) - Saraon, Punit; Snider, Jamie; Schormann, Wiebke; Rai, Ankit; Radulovich, Nikolina; Sánchez-Osuna, Maria; Coulombe-Huntington, Jasmin; Huard, Caroline; Mohammed, Mohammed; Lima-Fernandes, Evelyne; Thériault, Brigitte; Halabelian, Levon; et al.
Graphical abstract: Highlights: CRISPR/Cas9 knockout screen identifies COPB2 as the EMI1 top resistance gene. EMI66 alters the electrophoretic mobility of COPB2 and downregulate RTK expression. EMI66 alters EGFR and COPB2 subcellular localization. COPB2 suppression alters ER stress response and RTK post-translational processing. EMI66 blocks proliferation of lung cancer cells and primary lung cancer organoids. Abstract: Activating mutations in the epidermal growth factor receptor (EGFR) are common driver mutations in non-small cell lung cancer (NSCLC). First, second and third generation EGFR tyrosine kinase inhibitors (TKIs) are effective at inhibiting mutant EGFR NSCLC, however, acquired resistance is a major issue, leading to disease relapse. Here, we characterize a small molecule, EMI66, an analog of a small molecule which we previously identified to inhibit mutant EGFR signalling via a novel mechanism of action. We show that EMI66 attenuates receptor tyrosine kinase (RTK) expression and signalling and alters the electrophoretic mobility of Coatomer Protein Complex Beta 2 (COPB2) protein in mutant EGFR NSCLC cells. Moreover, we demonstrate that EMI66 can alter the subcellular localization of EGFR and COPB2 within the early secretory pathway. Furthermore, we find that COPB2 knockdown reduces the growth of mutant EGFR lung cancer cells, alters the post-translational processing of RTKs, and alters the endoplasmic reticulum (ER) stress response pathway. Lastly, we show that EMI66 treatment also alters the ER stress response pathway and inhibits the growth of mutant EGFR lung cancer cells and organoids. Our results demonstrate that targeting of COPB2 with EMI66 presents a viable approach to attenuate mutant EGFR signalling and growth in NSCLC.